Integration of chromatin accessibility and gene expression reveals new regulators of cold hardening to enhance freezing tolerance in Prunus mume. (19th January 2023) - Li, Ping; Zheng, Tangchun; Li, Lulu; Liu, Weichao; Qiu, Like; Ahmad, Sagheer; Wang, Jia; Cheng, Tangren; Zhang, Qixiang
Abstract: Low temperature is one of the most important abiotic factors limiting the growth, development and geographical distribution of plants. Prunus mume is an attractive woody ornamental plant that blooms in early spring in Beijing. However, the molecular mechanisms underlying cold hardening to enhance freezing tolerance in Prunus genus remains elusive. This study examined the dynamic physiological responses induced by cold hardening, and identified freezing-tolerance genes by RNA-seq and ATAC-seq analyses. Cold hardening elevated the content of soluble substances and enhanced freezing resistance in P. mume . Transcriptome analysis indicated that the candidate differentially expressed genes (DEGs) were those enriched in Ca 2+ signalling, mitogen-activated protein kinase (MAPK) cascade, abscisic acid signalling, and inducer of CBF expression 1 (ICE)-C-repeat binding factor (CBF) signalling pathways. The openness of gene chromatin positively correlated with the expression level of these genes. Thirteen motifs were identified in the open chromatin regions in the treatment group subjected to freezing after cold hardening. The chromatin opening of transcription start site at the proximal –177 region of cold-shock protein CS120-like ( PmCSL ) was markedly increased, while the expression level of PmCSL was significantly up-regulated. Overexpression of PmCSL in Arabidopsis significantly improved the freezing tolerance of transgenic plants. These findings provide new insights into the regulatory mechanism of freezing tolerance to improve breeding of cold-hardy P. mume plants. Abstract : Integrated analysis of RNA-seq and ATAC-seq reveals the molecular mechanism of cold hardening to enhance freezing tolerance, and the function of a new regulator, PmCSL, in Prunus mume .